Letter (copy) : Goods for Basque Children's Homes - Tewson, Vincent
1938-06-21 038-0137-001 Secretary's. HVT/FC/462. BLA/GMN 21st June, 1938. Miss B.L. Arne, The Basque Children's Committee, 53, Marsham Street, S.W.1. Dear Miss Arne, GOODS FOR BASQUE CHILDRENS' HOMES. I thank you for your letter of the 17th instant. I have to-day sent your order to Mr. Newman with a request that delivery should be made as early as possible to the Homes in question. Yours sincerely, Assistant Secretary. 292/946/38/137(I)